2021
DOI: 10.1038/s42003-021-02260-5
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin signaling modulates aging-associated metabolic network integrity in response to nutrient choice in Drosophila melanogaster

Abstract: Aging arises from complex interactions among multiple biochemical products. Systems-level analyses of biological networks may provide insights into the causes and consequences of aging that evade single-gene studies. We have previously found that dietary choice is sufficient to modulate aging in the vinegar fly, Drosophila melanogaster. Here we show that nutrient choice influenced several measures of metabolic network integrity, including connectivity, community structure, and robustness. Importantly, these ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Dietary options have been reported to reduce life expectancy in Drosophila , and the 5HT2a receptor is one of the main culprits due to its role in establishing the protein value of meals (Ro et al 2016 ). In this way, the interruption of their signaling eliminated the mortality differences between the two dietary environments and a change in the state of metabolic networks was observed throughout the organism from a fragmented, fragile and vulnerable to perturbations to a highly connected and robust one (Lyu et al 2021b , a ). Notably, experimental trials with Caenorhabditis found that mutations affecting the enzymes that regulate its biosynthesis and serotonin transporters produce small or modest effects on its lifespan.…”
Section: Gpcr Influencing Lifespanmentioning
confidence: 99%
“…Dietary options have been reported to reduce life expectancy in Drosophila , and the 5HT2a receptor is one of the main culprits due to its role in establishing the protein value of meals (Ro et al 2016 ). In this way, the interruption of their signaling eliminated the mortality differences between the two dietary environments and a change in the state of metabolic networks was observed throughout the organism from a fragmented, fragile and vulnerable to perturbations to a highly connected and robust one (Lyu et al 2021b , a ). Notably, experimental trials with Caenorhabditis found that mutations affecting the enzymes that regulate its biosynthesis and serotonin transporters produce small or modest effects on its lifespan.…”
Section: Gpcr Influencing Lifespanmentioning
confidence: 99%
“…Particularly, the modulation of serotonin on feeding-related processes has been intensively studied in several insect species, including locust, aphid ( Kaufmann et al, 2004 ), bugs ( Orchard, 2006 ), bees ( French et al, 2014 ), mosquitoes ( Novak and Rowley, 1994 ), and flies ( Haselton et al, 2009 ; Albin et al, 2015 ; Schoofs et al, 2018 ; Lyu et al, 2021 ). The serotonergic modulation is involved in feeding states, e.g., hunger and satiety and in a sequence of discrete events of feeding, such as, food detection, salivary secretion, food intake, and ingestion of food ( Tierney, 2020 ).…”
Section: Introductionmentioning
confidence: 99%